2009
DOI: 10.1111/j.1744-7429.2008.00484.x
|View full text |Cite
|
Sign up to set email alerts
|

Reproduction in Wild Populations of the Threatened TreeMacadamia tetraphylla: Interpopulation Pollen Enriches Fecundity in a Declining Species

Abstract: Macadamia tetraphylla is a subtropical rain forest tree from fragmented lowlands in eastern Australia. Owing to habitat loss and fragmentation, this commercially important species is vulnerable to extinction. Breeding system and fecundity were investigated in nine populations incorporating three habitat types (moderately disturbed, highly disturbed, and intact) to determine if seed set, seed weight, and genetic diversity are compromised by disturbance. Breeding success was also tested using pollen donors from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…All four Macadamia species usually occur in small populations in the native ecosystem and are at risk of extinction (Pisanu et al ., ). Unlike M. ternifolia and the cultivated species M. tetraphylla and M. integrifolia where large genetic diversity exists (Steiger et al ., ; Peace et al ., ), genetic diversity in M. jansenii is low and subpopulations show little genetic differentiation (Shapcott & Powell, ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…All four Macadamia species usually occur in small populations in the native ecosystem and are at risk of extinction (Pisanu et al ., ). Unlike M. ternifolia and the cultivated species M. tetraphylla and M. integrifolia where large genetic diversity exists (Steiger et al ., ; Peace et al ., ), genetic diversity in M. jansenii is low and subpopulations show little genetic differentiation (Shapcott & Powell, ).…”
Section: Discussionmentioning
confidence: 97%
“…Although all accessions of M. tetraphylla and M. integrifolia used in commercial productions have been selected from the native environments in Australia, wild macadamia populations represent a significant resource for the macadamia industry as potential sources of resistance to biotic and abiotic stress, and for improving yield and breeding efficiencies. These wild accessions are vulnerable to extinction due to habitat loss and fragmentation (Pisanu et al ., ; Neal et al ., ; Powell et al ., ). In addition to these two major threats, a large number of native plant species are threatened by P. cinnamomi in Australia (Kueh et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent work on Macadamia tetraphylla L.A.S.Johnson (Pisanu, Gross & Flood, 2009), which is weakly self‐compatible, has indicated that the situation is perhaps even more complex than Darwin could have imagined. In experiments using trees from highly disturbed to intact habitats, and using pollen from donors located at distances from less than 10 m to up to 100 km distance, plants artificially pollinated using outcrossed pollen produced more seed per raceme than did open‐pollinated or self‐pollinated trees.…”
Section: What Did Darwin Discover? a Summary Of The Results And Discumentioning
confidence: 99%
“…But up to now, the genome sequencing of M. tetraphylla has not yet been reported. As an important parent species of macadamia varieties in production 23 , the genome sequencing of M. tetraphylla will lay a good foundation for macadamia breeding. Table 1 and Fig.…”
mentioning
confidence: 99%